1998
DOI: 10.1002/(sici)1096-9071(199805)55:1<24::aid-jmv5>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

HCV antibodies in saliva and urine

Abstract: Infection with hepatitis C virus (HCV) is usually established by detection of serum antibodies (anti-HCV). This study was conducted in order to evaluate whether saliva and urine may substitute serum for anti-HCV detection. Serum, saliva, and urine were obtained simultaneously from 141 patients with a variety of liver diseases and from 52 patients with autoimmune diseases (systemic lupus erythematosus n = 27 and rheumatoid arthritis n = 25). The cell free fraction of saliva and urine samples was tested for anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…In previous studies using Salivette samples, the sensitivities and specificities varied between 71 and 94.4% and 93 and 100%, respectively, depending on the detection method chosen (3, 4, 15, 29, 31, 33). Regarding spitting samples, in the present study, the sensitivity and specificity were 90.9 and 95.24, respectively, whereas in other studies, the sensitivities and specificities range from 0 to 90% and 100%, respectively, using immunochromatographic or chemiluminescence assays (2, 30). These results demonstrated the importance of defining the best collection and detection method for saliva samples.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In previous studies using Salivette samples, the sensitivities and specificities varied between 71 and 94.4% and 93 and 100%, respectively, depending on the detection method chosen (3, 4, 15, 29, 31, 33). Regarding spitting samples, in the present study, the sensitivity and specificity were 90.9 and 95.24, respectively, whereas in other studies, the sensitivities and specificities range from 0 to 90% and 100%, respectively, using immunochromatographic or chemiluminescence assays (2, 30). These results demonstrated the importance of defining the best collection and detection method for saliva samples.…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, few false‐positive or false‐negative results were observed when the optimum cut‐off value was determined using the ROC curve, and discordant saliva results (in relation to the serum samples) were observed for 5.2% (5/96) of the study population. False‐positive saliva test results were presented only in spitting samples, which may have been attributed to non‐specific interaction between HCV antigen and saliva elements, as has been demonstrated in previous studies (2, 30). The false‐negative salivary test results may reflect the low concentration of antibodies in the saliva samples (11–13).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Presence of helicobacter pylori in saliva is a sign of peptic ulcer 19,20 . Saliva can be used as a tool for the detection of dental plaque -induced diseases, i.e.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Assays for detecting anti-HCV in DBS and saliva have reported sensitivities ranging from 70% to 100% and specificities from 87.5% to 100%. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] The differences observed are related to the population studied, saliva collection, type of assay, and modifications in cut-off calculation, incubation of sample and sample volume. The influence of HIV infection on anti-HCV testing in saliva samples was previously evaluated, but a low number of individuals were recruited 26 or the influence of HIV viral load and CD4 cell count were not determined.…”
mentioning
confidence: 99%